Analisis Dominansi Spesies Bintang Laut di Kawasan Pantai Awang Kabupaten Lombok Tengah - Hariyati, Astri (Biocaster : Jurnal Kajian Biologi, 2025)
This research aims to analyze the dominance of starfish species in the Pantai Awang area, Central Lombok Regency. The type of this research is exploratory descriptive research. This study uses purposive sampling method with 3 stations, 5 transects, and 4 plots. The data collection techniques used were observation and documentation. The data analysis technique used is the dominance index. The results of the research conducted show that the highest dominance is found in the species Protoreaster nodosus, with a dominance index value of 0.857, categorized as moderate dominance, meaning there is light dominance where the development of species is quite balanced. Meanwhile, Archaster typichus and Linckia laevigata have dominance index values of 0.114 and 0.028, categorized as low dominance, meaning there is no dominance with balanced species development. Thus, it can be concluded that in the studied ecosystem, Protoreaster nodosus tends to be more dominant compared to Archaster typichus and Linckia laevigata, but there is no species that is so dominant as to disturb the balance of the ecosystem.